Tazarcus, a new phylogenetically unplaced genus of two flightless weevils with metapleural ridge from the Eastern Arc Mountains, Tanzania (Coleoptera: Curculionidae: Molytinae) - Grebennikov, Vasily V. (Zootaxa, 2020)
This paper reports new flightless forest litter weevils discovered in Tanzania. They are classified into two species of the genus Tazarcus gen. nov.: T. aeaea sp. nov. (the type species; from South Pare and West Usambara) and T. ogygia sp. nov. (Rubeho). Both new species inhabit the archipelago-type Eastern Arc Mountain rainforests renowned for the high diversity of their biota. Adults of Tazarcus are recognizable by their relatively small size (length of pronotum and elytra in dorsal view 2.0–3.4 mm), the short and straight rostrum covered dorsally with dense velvety pilosity, an antennal funicle with seven segments, a prosternal canal, procoxae separated, a lack of hind wings and effaced elytral shoulders. Remarkably, adults of Tazarcus possess a short longitudinal ridge on each metapleuron, which bears a line of serration likely homologous to sclerolepidia. A phylogenetic analysis of 72 terminals and 3134 aligned positions from one mitochondrial and two nuclear ribosomal fragments corroborated the monophyly of the new genus, of both new species and of all three sampled populations but did not identify the sister group of Tazarcus. Three other weevil taxa with adults possessing a similarly shaped metapleural ridge (the African Thrombosternus Marshall and Allocycloteres Voss and an unidentified species of Molytinae from Madagascar) did not cluster with Tazarcus, suggesting multiple origins of this structure. Tazarcus is taxonomically classified as incertae sedis in a non-monophyletic subfamily “Molytinae”. Images and DNA sequences of all 72 herein analysed specimens are available online at dx.doi.org/10.5883/DS-VGDS011.